2016
DOI: 10.1016/j.fertnstert.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Are proton-pump inhibitors harmful for the semen quality of men in couples who are planning pregnancy?

Abstract: The use of PPIs in the period 12 to 6 months preceding semen analysis is associated with a threefold higher risk of low TMSC, which suggests that a long-term increase in gastric pH results in a decline of sperm quality. This finding emphasizes the need for more preconceptional research and counseling on the potential effects of medication use on semen quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…In contrast, a case–control study conducted by Huijgen et al concluded that the use of proton pump inhibitors in the period 6–12 months preceding seminal fluid analysis was found to be correlated with a threefold higher risk of low total motile sperm count (Huijgen et al, ). These findings suggest that a long‐term increase in stomach acidity may result in a reduction of semen quality, and hence the fertilising ability (Huijgen et al, ). Actually, this study was a case–control study of a population‐based registry (data from between 1996 and 2013), and comprising 2,473 human males from couples planning pregnancy, and some of them ( n = 241) with a low total motile sperm count.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, a case–control study conducted by Huijgen et al concluded that the use of proton pump inhibitors in the period 6–12 months preceding seminal fluid analysis was found to be correlated with a threefold higher risk of low total motile sperm count (Huijgen et al, ). These findings suggest that a long‐term increase in stomach acidity may result in a reduction of semen quality, and hence the fertilising ability (Huijgen et al, ). Actually, this study was a case–control study of a population‐based registry (data from between 1996 and 2013), and comprising 2,473 human males from couples planning pregnancy, and some of them ( n = 241) with a low total motile sperm count.…”
Section: Discussionmentioning
confidence: 96%
“… 5 In contrast, however, PPI use was recently linked to lower total motile sperm count (TMSC) in couples planning for pregnancy. 6 Understanding the effects of PPIs on semen is important in counseling subfertile men, considering the high rates of PPI use in the general population. Given the scarcity of evidence and the controversies in the literature, we aimed to assess the effects of PPI use on semen parameters using data from a large population of subfertile men.…”
Section: Introductionmentioning
confidence: 99%
“…Miscarriage, proliferative changes, increased levels of chromogranin A, increased levels of fibroblast growth factor 2, chills, cardiovascular events (myocardial infarction, heart failure, stroke, ischemic stroke, pulmonary embolism and thrombosis), scarlet fever, hyperglycemia, mononucleosis infection, gastrointestinal bleeding, nasopharyngitis, otitis media, loss of libido, rhinitis, dementia, metabolic syndrome and hepatic steatosis, low sperm motility, increased risk of fibrosis progression, cirrhosis, hepatic decompensation and development of hepatocellular carcinoma. [44][45][46][47][48]60,[65][66][67] DI (n = 6)…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the adverse events reported were already known, unexpected events such as dementia, 44 low-motility sperm, 46 miscarriage, proliferative changes, 5 increased levels of chromogranin A, 79 increased levels of fibroblast growth factor 2, 72 chills, cardiovascular events (myocardial infarction, heart failure, stroke, ischemic stroke, pulmonary embolism and thrombosis), 47 scarlet fever, hyperglycemia, mononucleosis infection, gastrointestinal bleeding, nasopharyngitis, otitis media, loss of libido and rhinitis have also been identified. 4,[65][66][67]102 Because the associations between these adverse events and use of omeprazole are not fully understood, there is a need to carry out further studies to investigate the relationships between omeprazole and these events.…”
Section: Discussionmentioning
confidence: 99%